Morphometrical and Immunohistochemical Evaluation of Kidney as an Indirect Parameter to Estimate Age in Puppies in Veterinary Forensic Pathology - Ilaria d’Aquino; Giuseppe Piegari; Gianluca Miletti; Emanuela Sannino; Dario Costanza; Leonardo Meomartino; Rosario Fico; Lorenzo Riccio; Emanuela Vaccaro; Davide De Biase; Orlando Paciello (Animals, 2023)
Estimation of age represents a central focus in the veterinary forensic pathology field. Currently, the visual examination of the dentition and the skeletal age are the main methods to estimate the age of puppies. Nevertheless, these methods are affected by a broad range of variables. In contrast, the kidney is characterized by a specific postnatal development. In human glomerulogenesis, fetal mesangial cells change their immunohistochemical phenotypes with maturation. Therefore, we hypothesized that histological and immunohistochemical examinations of the kidney can be used together as an indirect parameter for age determination in puppies’ cadavers. Forty-five puppies’ cadavers were divided into five groups defined by age (Group A= 0–15 days, Group B = 16–45 days, Group C = 46–85 days, Group D = 86–105 days, Group E= 105–365 days). For each case, kidney samples were collected and processed for histopathological (for morphometrical study of the glomerulus) and immunohistochemical (for the immunolocalization of the α-SMA protein) studies. Morphometrical study allowed us to observe statistical differences in the mean glomerulus numbers per field among assessed groups. Similarly, immunohistochemical examination showed differences in SMA expression among groups. Our findings suggest a potential use of kidney morphometrical and immunohistochemical examinations together as an indirect parameter to assess the age of illegally imported puppies.